Effect of Fertilization with N-Inhibitors on Root and Crop Development of Flaxseed Crop (Linum usitatissimum L.) - Ioanna P. Kakabouki; Stella Karydogianni; Charikleia Zisi; Antigolena Folina (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Flax is a crop whose products can be used in a variety of ways such as industrial use, human consumption, and fiber production. Nitrogen appears to have a positive effect on flaxseed growth and production. In an experiment conducted in two consecutive years in Greece, it has been studied how three combinations of urea fertilization affect flaxseed cultivation (cv. ‘Everest’). More specifically, the experimental treatments with urea fertilizers were represented as follows: only urea; urea with urease inhibitor; and urea with urease inhibitor and nitrates inhibitors. The value of root mass ranged from 0.780 to 1.182 mg/cm3 in the first year and from 0.872 to 1.267 mg/cm3 in the second year. The maximum value of plant height was 69.25 in urea with double inhibitors. Leaf Area Index (LAI) was double in fertilized plots compare to unfertilized. Oil content was significantly affected by year and noticed mostly 1% among treatments. Oil yield was affected by fertilizers and the maximum value was 513.96 kg/ha. A positive significant correlation coefficient was observed between oil yield and LAI (r=0.8699). A positive correlation was noticed between seed yield and NUE (r=0.6881). The most beneficial effects were mentioned under urea with UI and NI inhibitors.